Advanced Technologies for Science and Engineering - Kannadhasan, S.; Nagarajan, R.; Karthick, Alagar; K. Saravanan, K.; Pal, Kaushik (Bentham Science Publishers, 2024)
This volume covers a wide array of topics related to research, technology and sustainability for technology researchers and educators. Chapter 1 explores the detection of fake news in a distributed environment. Material science is covered in Chapter 2, which explains the influence of MOS2, B4C, and graphite on the mechanical and dry sliding wear behavior of aluminum 7075 hybrid matrix composites. Chapter 3 focuses on sensors and antennas for smart sensor networks. Chapters 4 to 8 delve into various aspects of electrical and computer engineering, including induction motor condition monitoring, automatic conversion of building plans to graphs for robot navigation, and analysis of defects in microscopic and electroluminescent images using AI and image processing algorithms.Chapters 9 to 16 cover topics such as missing data prediction techniques, breast cancer diagnosis on mammography, groundwater contamination, biofertilizers, organic farming, and remediation using organisms. Sustainable development is a key theme in Chapters 17 to 26, addressing issues like sensor-based vehicle fuel theft detection, waste management techniques, bioremediation of soil contaminated with heavy metals, sustainable agriculture practices, and novel approaches in bioplastics and nanoremediation. Finally, Chapters 27 to 29 touch upon renewable energy and Industrial IoT, discussing research challenges in renewable energy sources, recent trends, and the transformation brought about by the Industrial Internet of Things.